Antithrombotic Effect of shRNA Target F12 Mediated by Adeno-Associated Virus - Li, Fanfan; Yang, Xiao; Liu, Jie; Shu, Kuangyi; Shen, Chenfang; Chen, Tao; Yang, Wei; Li, Shanshan; Wang, Xiaoou; Jiang, Minghua (Molecular therapy. Nucleic acids, 2019)
Coagulation factor XII (FXII) plays a crucial role in thrombosis. Moreover, deficiencies in FXII are not associated with excessive bleeding, and its depletion exhibits satisfactory protective effect on thrombus formation. Several strategies targeting FXII have been applied to inhibit thrombosis formation. In this study, C57BL/6 mice were injected with adeno-associated virus (AAV) to identify the role of short hairpin RNA (shRNA) in thrombosis. Differences in liver FXII, coagulation function, and thrombus formation were detected. The potential side effects of FXII were then evaluated through analysis of tail bleeding, biochemical indices, and pathological sections. Results showed that shRNAs, especially shRNA2, carried by AAV, effectively reduced the expression of FXII. Furthermore, only shRNA2 demonstrated an anti-thrombosis effect on multiple models without hemorrhage and side effects. Hence the novel approach of AAV-based shRNA is specific and safe for inhibiting FXII and thrombosis.